IMPLEMENTATION OF THE ANALYTICAL HIERARCHY PROCESS METHOD IN THE SELECTION OF PROSPECTIVE SCHOLARSHIP RECIPIENTS - Purwanto, Heru; Lase, Marianus (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
Student achievement is a barometer of success in teaching and learning activities. One way that can be done to motivate students to improve learning achievement is to provide scholarships as a form of appreciation from the institution or educational institution where they study. Through the Decision Support System (SPK) can assist leaders in making the right decisions for the selection and awarding of scholarships based on predetermined criteria. The purpose of this research provides more important criteria for determining selection alternatives for prospective beasiswa recipients. This research uses the Analytical Hierarchy Process (AHP) Method. Pairwise comparisons are given to derive the importance of the criteria. Cumulative Achievement Index (GPA), Economic Situation and Non-Academic Achievement. The criteria for economic conditions have sub-criteria for pairwise comparison in the form of parental income and number of siblings, while achievements have sub-criteria whether they have achievements both locally, nationally and internationally or not have achievements. Comparison of paired criteria where GPA has the largest value of 0.63 followed by achievement with a value of 0.26 and economic conditions with a value of 0.11., so that from the calculation results of three alternatives obtained the top rank with a value of 0.531337